A model-based method for the design of intermittent pneumatic compression systems acting on humans. (February 2014) - Ferraresi, Carlo; Maffiodo, Daniela; Hajimirzaalian, Hamidreza
Intermittent pneumatic compression is a well-known technique, which can be used for several therapeutic treatments like sports recovery, lymphoedema drainage, deep vein thrombosis prevention or others, which may require very different operating characteristics as regards the desired pressure values and the operating velocity. The performance and the effectiveness of the device are often difficult to predict and must be usually optimized through empirical adjustments. This article presents a general method based on the mathematical modelling of a generic IPC system, aimed at studying and developing such a device with physical and dynamical characteristics suitable for the intended application.